2021
DOI: 10.1186/s12864-021-07387-7
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of CNVs in Chinese indigenous fine-wool sheep populations using whole-genome resequencing

Abstract: Background Copy number variation (CNV) is an important source of genetic variation that has a significant influence on phenotypic diversity, economically important traits and the evolution of livestock species. In this study, the genome-wide CNV distribution characteristics of 32 fine-wool sheep from three breeds were analyzed using resequencing. Results A total of 1,747,604 CNVs were detected in this study, and 7228 CNV regions (CNVR) were obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
6
15
1
Order By: Relevance
“…Chromosome 26 had the smallest number of CNVRs. This observation was in agreement with Yuan et al 50 where they reported that the chromosome length had a significant positive linear relationship with the number of CNVRs (R 2 = 0.87) with the maximum found in chromosome 1 and the minimum found on 26. Conflicting results have also reported by Jenkins et al 43 in Texel, Coopworth, Perendale, Romania, and Merino sheep and Zhu et al 48 , in the study of CNVR-containing genomic regions in Tibetan sheep, stated that chromosome 3 had the highest number of CNVRs.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Chromosome 26 had the smallest number of CNVRs. This observation was in agreement with Yuan et al 50 where they reported that the chromosome length had a significant positive linear relationship with the number of CNVRs (R 2 = 0.87) with the maximum found in chromosome 1 and the minimum found on 26. Conflicting results have also reported by Jenkins et al 43 in Texel, Coopworth, Perendale, Romania, and Merino sheep and Zhu et al 48 , in the study of CNVR-containing genomic regions in Tibetan sheep, stated that chromosome 3 had the highest number of CNVRs.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, the CNVRs detected in this study were compared with the QTLs reported in the sheep QTL database. The QTL categories found in this study were basically identical to those found in previously reported studies 50 , 52 , 71 . For example, the health-related QTLs found included fecal egg count QTLs, and worm count QTLs that previous studies have reported that worm disease infection rates in sheep can exceed 70% in many countries, causing huge losses to the livestock industry 72 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…While many CNVs are known since almost 2 decades for European population, recent widespread application of chromosomal microarray analysis (CMA) in diagnosis in China revealed many new CNVs. Overall, clinical significance of these new CNVs needs to be still some considerations [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%